Inclusive Villages and Creative Economy Development: Analysis of Social Capital in MSME Communities in Sidoarjo Regency - Tuti Budirahayu; Rafi Aufa Mawardi; Sutinah; Fitri Mutia; Endah Rahayu (Jurnal Mengkaji Indonesia, 2025)
Abstract: Participatory creative economic development can be realized through inclusive villages. Inclusive villages are a transformative and modern village concept that accommodates the interests of people with disabilities in socio-economic practices. However, there are still challenges and problems in realizing inclusive villages, which are inherent in creative economic dimensions. Purpose: This study aims to analyze social capital within the MSME community in Sidoarjo Regency, providing a basis for achieving inclusive villages and fostering a creative economy. Design/Methodology/Approach: This study employed qualitative descriptive methods in Dukuh Tengah Village, Sidoarjo Regency. Then, observation and in-depth interviews were used as data collection techniques with 30 informants who were recipients of the KURMA program. Findings: This study found that the informants’ perspectives and understanding of inclusive villages and the creative economy were excellent. Apart from that, this study analyzes four opportunities to realize a just creative economy: the majority of people are entrepreneurs, have a good understanding of inclusive villages and the creative economy, get assistance from the KURMA program, and have good digital literacy. This study explains that the dimensions of trust, values, norms, and strong social networks in the community in Dukuh Tengah Village largely determine social capital in the MSME community. Therefore, this becomes the primary basis for creating inclusive villages, which are inherently tied to creative economic aspects. Originality/value: This study contributes to analyzing the challenges and potential that exist in Dukuh Tengah Village to create an inclusive village. It also successfully analyzed the dimensions of social capital present in Dukuh Tengah Village, serving as a basis for creating a creative village that is inclusive of people with disabilities.